The laboratory rat - Sharp, Patrick E.; La Regina, Marie C.; Suckow, Mark A. (Boca Raton CRC Press, 1998)
This guide was created especially for individuals performing research with rats whose duties include animal facility management, animal husbandry, regulatory compliance, and technical procedures involved with their research. Basic information and common procedures are presented in detail.
1. Important Biological Features -- 2. Husbandry -- 3. Management -- 4. Veterinary Care -- 5. Experimental Methodology -- 6. Resources.
Includes bibliographical references (p. 179-197) and index.
Keywords: Rats as laboratory animals